Diterpenes from Pinus kesiya var. langbianensis (A.Chev.) Gaussen ex Bui (Pinaceae) and their protective effects in LPS-treated BEAS-2B cells. (November 2022) - Liu, Yu-Fei; Song, Zhi-Min; Zeng, Meng-Nan; Wang, Yan-Zhi; Cheng, Yong-Xian; Qiao, Lin-Qing; Peng, Rui; Feng, Wei-Sheng
Abstract: Eight previously undescribed diterpenoids, rosins A−H, and nine known diterpenoids were isolated from the resin from Pinus kesiya var. langbianensis (A.Chev.) Gaussen ex Bui (Pinaceae) extracted with 95% ethanol. Their structures were determined by nuclear magnetic resonance spectroscopy, mass spectrometry, J −based configuration analysis (JBCA), NOESY spectra, calculated NMR chemical shifts and electronic circular dichroic (ECD) spectra. All compounds were evaluated for their protective effects in LPS-treated human normal lung epithelial cells (BEAS-2B), and the cell viability was significantly increased after treatment with compounds 5, 10, 12, or 15  at a concentration of 10  μ M. Graphical abstract: Seventeen diterpenoids were isolated and identified from Pinus kesiya var . langbianensis (A.Chev.) Gaussen ex Bui (Pinaceae) by comprehensive methods. Four compounds showed significant protective effects in LPS-treated BEAS-2B cells. Image 1 Highlights: Pine resin was isolated by cold extraction to avoid high temperature. Eight undescribed diterpenoids had been isolated and identified from pine resin. The stereochemistry structure were determined by NMR calculation and ECD calculation. Four compounds showed significant protective effects in BEAS-2B cells.